2002
DOI: 10.1002/jsfa.1237
|View full text |Cite
|
Sign up to set email alerts
|

Development changes of anthocyanins in Vitis vinifera grapes grown in the Douro Valley and concentration in respective wines

Abstract: Grapes of Touriga Nacional and Touriga Francesa red Vitis vinifera varieties have been sampled from two vineyard sites at different altitudes during three consecutive vintage years (1997, 1998 and 1999) in the Douro Valley. The total anthocyanidin monoglucosides (AMGs) detected by HPLC/DAD and the red colour of grape skin extracts were monitored during the last month of maturation. Microvinifications were performed with the grapes studied and the resulting Port wines were analysed. Malvidin 3-glucoside and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 23 publications
3
81
0
4
Order By: Relevance
“…Cooler ambient temperatures tend to favour accumulation of anthocyanins in berry skins and the resulting wines (Bergqvist et al, 2001;Mateus et al, 2002;Miguel-Tabares et al, 2002;Spayd et al, 2002) as also found in this study for Pinotage wines. Sunlight exposure, however, increases anthocyanin concentration in grapes (Kliewer, 1970;Crippen & Morrison, 1986;Spayd et al, 2002).…”
Section: Effect Of Climatic Regionsupporting
confidence: 77%
“…Cooler ambient temperatures tend to favour accumulation of anthocyanins in berry skins and the resulting wines (Bergqvist et al, 2001;Mateus et al, 2002;Miguel-Tabares et al, 2002;Spayd et al, 2002) as also found in this study for Pinotage wines. Sunlight exposure, however, increases anthocyanin concentration in grapes (Kliewer, 1970;Crippen & Morrison, 1986;Spayd et al, 2002).…”
Section: Effect Of Climatic Regionsupporting
confidence: 77%
“…This could be related to the high-altitude climate. A few observations have mentioned that high-altitude cultivation strongly alters solar radiation, temperature and other environmental factors around grapevines (Mateus et al, 2002). A higher altitude generally corresponds to stronger sunlight (Cortell & Kennedy, 2006;Fanzone et al, 2010), lower temperature and humidity (Ojeda et al, 2002;Castellarin et al, 2007), greater temperature difference between day and night, and more extreme environmental conditions (Mateus et al, 2001), all of which are important factors affecting the production of flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…(Hunter et al, 1995;Haselgrove et al, 2000;Mateus et al, 2001Mateus et al, , 2002Ojeda et al, 2002;Deloire et al, 2005;Downey et al, 2005;Petrie & Clingeleffer, 2006;Poni et al, 2006;Castellarin et al, 2007;Cortel et al, 2007;Bindon et al, 2008;Holt et al, 2008;Tarara et al, 2008;Hanlin et al, 2009;Chorti et al, 2010;Hunter et al, 2010). Furthermore, these factors may also affect berry size and modify proportions of skin, flesh and seed in the grapevine berry.…”
Section: Introductionmentioning
confidence: 99%